A cooking machine. - Shamsuddin, Rosnah (2010)

(untitled)
The present invention generally relates to a machine for cooking rice in huge volume. The cooking process begins by first setting the desired parameters including temperature of steam and hot water, volume of steam and hot water that corresponds to the speed of an auger (501) and a screw (113). The cooking material is then fed into an inlet (103). The cooking process then continues with cooking material flows uniformly into a cooking house (101). The cooking material supplied with direct heat from steam and hot water sprayed for absorption by the cooking house (101). Additional heat is also available from a heating system to ensure the cooking material is fully cooked and also for temperature maintenance. The cooking material is gradually cooked as it is being conveyed. At the end of the process fully cooked cooking material is obtained.